Paulus as vredemaker. Oor die resepsie van die Brief aan Filemon in die vierde en vyfde eeu n.C - Tolmie, D. F. (HTS teologiese studies, 2015)
Paul, the peacemaker. On the reception of the Letter to Philemon in the 4th and 5th centuries AD. By means of his letter to Philemon Paul attempted to make peace between Philemon and his slave, Onesimus. The theological aspects of this endeavour have been discussed often in academic circles, but thus far little attention has been given to what the practical implications of this would have been for Philemon’s household. In this article, this issue is addressed from a particular perspective, namely how this aspect was interpreted by Christians in the 4th and 5th centuries CE. The interpretations of the Letter to Philemon by Ambrosiaster, Jerome, John Chrysostom, Pelagius, Theodore of Mopsuestia and Theodoret of Cyrus are then investigated systematically in order to determine what their views were in this regard. It is shown that they all agreed that Philemon would (or would have no choice but to) forgive Onesimus, and that Onesimus would have turned into a better slave. All of these interpreters agreed that there would not be any drastic social changes in Philemon’s household although it does seem as if one of them, Ambrosiaster, realised that what Paul expected of Philemon could have had serious consequences for the relationship between Philemon and Onesimus.